1963
DOI: 10.1017/s0003356100021474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertiliser nitrogen and herbage dry-matter content on herbage intake and digestibility in bullocks

Abstract: SUMMARY1. Two experiments were conducted, the first during May, July and August, 1958, and the second during August 1960. The first experiment measured the intake and digestive efficiency of cattle fed on fresh cut herbage from low-and high-nitrogen manuring treatments with and without irrigation. The second experiment tested the effect of water added to fresh cut herbage on the intake of cattle.2. Rainfall during the summer of the first experiment was high and irrigation had no effect on any of the criteria u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1969
1969
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…The efifect of N on digestibility has been found to be small, according to Dent and Aldrich (6) and Minson, Raymond and Harris (18). However, Holmes and Lang (10) found that the digestibility of a mixed grass/clover sward was significantly increased by increasing the N level from 116 to 410 lb/ac. In contrast, McCarrick and Wilson (16) found that the application of 46 and 92 Ib N/ac reduced the digestibility of mixed swards by 2'15% and 2-33%, compared to swards receiving no N. Barlow (2) also reported a reduction in the digestibility of herbage with increasing N levels.…”
Section: The Effect Of Cumng Height and Nitrogen Level On The Yield mentioning
confidence: 99%
See 1 more Smart Citation
“…The efifect of N on digestibility has been found to be small, according to Dent and Aldrich (6) and Minson, Raymond and Harris (18). However, Holmes and Lang (10) found that the digestibility of a mixed grass/clover sward was significantly increased by increasing the N level from 116 to 410 lb/ac. In contrast, McCarrick and Wilson (16) found that the application of 46 and 92 Ib N/ac reduced the digestibility of mixed swards by 2'15% and 2-33%, compared to swards receiving no N. Barlow (2) also reported a reduction in the digestibility of herbage with increasing N levels.…”
Section: The Effect Of Cumng Height and Nitrogen Level On The Yield mentioning
confidence: 99%
“…The increase in yield of DM ceases to be linear before the yield of herbage N is similarly affected, this being at least partly due to the increased N content of the herbage (22,26). However, herbage digestibility is affected only slightly by N application;, and decreased digestibility (2) and increased digestibility (10) have been reported from increased applications of N. Increasing the frequency of defoliation normally results in lower yields of herbage DM (1,3,20), but digestibility and N content of the herbage are increased (13,19).…”
Section: Introductionmentioning
confidence: 99%
“…Neither DM content nor dry matter intake of lambs were affected by treatment (Table 1). Holmes & Lang (1963) found that DM intakes were similar for both herbages tested by them, even though the DM content of herbage from their high N fertilization treatment was consistently lower than that from their low N treatment (16.5% vs. 19.7%).…”
Section: Resultsmentioning
confidence: 82%
“…However, when they are restricted to one or the other herbage treatment, feed consumption is comparable ( 8,9, 1 0 ) . The use of N fertilizer on grass versus the use of legumes to fix atmospheric N has been a controversial topic for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the economic considerations and the yield of dry matter per area of land, the efiect on the efficiency of the animal must be considered. Blaser (2) and Holmes and Lang (8) cite several experiments in which output per animal tended to be higher for animals grazirrg grass-legume mixtures compared with N-fertilized grass, possibly because of higher soluble carbohydrates and unknown beneficial effects from the legumes (2). Another explanation is the slower rate of decline in digestibility of white clover compared with grass due to increasing maturity (7).…”
Section: Introductionmentioning
confidence: 99%